How (not) to be secular : reading Charles Taylor - Smith, James K. A., 1970- (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2014)
This book is a smart, intelligent guide to navigating today's culture. How (Not) to Be Secular is what Jamie Smith calls "your hitchhiker's guide to the present." It is both a reading guide to Charles Taylor's monumental work A Secular Age and philosophical guidance on how we might learn to live in our times. Taylor's landmark book A Secular Age (2007) provides a monumental, incisive analysis of what it means to live in the post-Christian present -- a pluralist world of competing beliefs and growing unbelief. Jamie Smith's book is a compact field guide to Taylor's insightful study of the secular, making that very significant but daunting work accessible to a wide array of readers. Even more, though, Smith's How (Not) to Be Secular is a practical philosophical guidebook, a kind of how-to manual on how to live in our secular age. It ultimately offers us an adventure in self-understanding and maps out a way to get our bearings in today's secular culture, no matter who "we" are -- whether believers or skeptics, devout or doubting, self-assured or puzzled and confused. This is a book for any thinking person to chew on. - Publisher.
Introduction : Our cross-pressured present : inhabiting a secular age -- Reforming belief : the secular as modern accomplishment -- The religious path to exclusive humanism : from deism to atheism -- The malaise of immanence : the "feel" of a secular age -- Contesting the secularization thesis -- How (not) to live in a secular age -- Conclusion : Conversions -- Glossary
Includes index.
Description based on vendor-supplied metadata.
Keywords: Taylor, Charles, -- 1931-; Christian philosophy; Christianity -- Philosophy; Secularism; Religion and culture; RELIGION / Christian Theology / Systematic; RELIGION / Christianity / General; Electronic books